Innate Lymphoid Cells in HIV/SIV Infections - Shah, Spandan V.; Manickam, Cordelia; Ram, Daniel R.; Reeves, R. Keith (Frontiers in Immunology, 2017)
Over the past several years, new populations of innate lymphocytes have been described in mice and primates that are critical for mucosal homeostasis, microbial regulation and immune defense. Generally conserved from mice to humans, innate lymphoid cells (ILC) have been divided primarily into 3 subpopulations based on phenotypic and functional repertoires: ILC1 bear similarities to natural killer (NK) cells; ILC2 have overlapping functions with TH2 cells; and ILC3 that share many functions with TH17/TH22 cells. ILC are specifically enriched at mucosal surfaces and are possibly one of the earliest responders during viral infections besides being involved in the homeostasis of gut-associated lymphoid tissue and maintenance of gut epithelial barrier integrity. Burgeoning evidence also suggests that there is an early and sustained abrogation of ILC function and numbers during HIV and pathogenic SIV infections, most notably ILC3 in the gastrointestinal (GI) tract, which leads to disruption of the mucosal barrier and dysregulation of the local immune system. A better understanding of the direct or indirect mechanisms of loss and dysfunction will be critical to immunotherapeutics aimed at restoring these cells. Herein, we review the current literature on ILC with a particular emphasis on ILC3 and their role(s) in mucosal immunology and the significance of disrupting the ILC niche during HIV and SIV infections.